Effects of Intravenous Immunoglobulin and Acyclovir in Preventing Neonatal Varicella - Waritsara Piyanonpong (Case Reports in Infectious Diseases)
Neonatal varicella mostly results from maternal varicella. The disease can cause presentation ranging from mild symptoms to varicella pneumonia, hepatitis, meningoencephalitis, or fatality. If the mother develops symptoms implying varicella 4–5 days antepartum to 2 days postpartum, the mortality rate of the baby may reach 20%. We report a case of neonatal varicella from maternal varicella. The patient’s mother initially developed maculopapular rash over her trunk 1 day after giving birth; she had a family member in the same household diagnosed with herpes zoster recently, and another member with diagnosed varicella, whose rash disappeared before the patient's birth. On the baby's third day of life, discrete vesicular rashes on erythematous background and discrete erythematous maculopapular rashes were found over his trunk, arms, and legs. The baby was subsequently diagnosed with neonatal varicella and was treated by intravenous immunoglobulin (IVIG) because there was no varicella zoster immunoglobulin (VZIG) available in the hospital, and also, intravenous acyclovir was given for 7 days. The rash completely resolved by the baby's fifth day of life, without any complications. The combination of IVIG and acyclovir might not effectively prevent neonatal varicella, but the medication could prevent the baby from developing serious complications and shorten the clinical course.